Funções executivas e perfil comportamental e socioemocional de crianças e adolescentes sobreviventes de tumores de fossa posterior - Ferreira, Daniele Caroline Leôncio (2021)
Despite the high number of cases of childhood cancer, especially in the last 30 years, the improvement and effectiveness of therapeutic strategies have resulted in an improvement in the prognosis and a significant increase in the survival rates of this population. However, in the case of posterior fossa tumors, the expression of cognitive, behavioral and socioemotional sequelae that impact these children's academic performance and quality of life is evident. Thus, the general objective of this study is to investigate the executive functions and the behavioral and social-emotional profile of children and adolescents surviving posterior fossa tumors. The research includes 2 relatively independent studies: (1) Working memory of children and adolescents surviving posterior fossa tumors; and (2) Inhibition, behavior and social skills of pediatric patients surviving posterior fossa tumors. 24 subjects surviving posterior fossa tumors aged 6-16 integrated clinical group in the first study. In the second study, 18 children and adolescents surviving posterior fossa tumors constituted clinical group and 18 subjects aged 6-16 formed a healthy control group, matched 1:1 according to sex, age, type of school and socioeconomic level. Participants were submitted to a neuropsychological assessment protocol, with results analyzed through descriptive and inferential statistical tools and clinical-qualitative analysis. In the first study, children and adolescents treated with chemotherapy and radiotherapy had more severe damage. Additionally, the data showed that children whose diagnosis and treatment of posterior fossa tumors occurred before the age of 5 years showed more accentuated impairments in the verbal working memory. In the second study, the results indicated that pediatric survivors of posterior fossa tumors present alterations in the inhibitory component, in social skills, in addition to the presence of behavior problems. More accentuated losses were verified in the group submitted to neurosurgery plus adjuvant therapy, when compared to the control group. Children and adolescents undergoing radiotherapy treatment showed a higher incidence of social withdrawal/depression, problems with social contact and attention fragility. It is expected to provide a better understanding of the nature and extent of the impact of the diagnosis and treatment of posterior fossa tumors on the cognitive, behavioral and socio-emotional development of the participants, who can serve health, education and family professionals who assist them. Therefore, it is intended to provide data that underlie the proposition of effective and less harmful treatments to the Central Nervous System and the development of intervention programs that minimize its adverse impacts, ensuring the children the full expression of their developmental potential.